EXPERIENCE IN USING INTRAVENOUS THROMBOLYSIS IN ISCHEMIC STROKE - T. V. Demin; M. V. Saikhunov; D. R. Khasanova (Неврология, нейропсихиатрия, психосоматика)
The authors' experience leads to the conclusion that intravenous thrombolytic therapy (TLT) is highly effective and should be introduced into the routine practical work of vascular departments. It is stressed that the success of this treatment for ischemic stroke in the therapeutic window period is associated with the adherence to the uniform patient selection criteria and management protocols after TLT; moreover, it is important to keep in mind the characteristics of each patient.